STUDY OF ANTI-INFLAMMATORY EFFECT OF COMPARATIVE DRUGS BY METHOD "COTTON PELLET" - Munira Allaeva; Malika YUnusova (International Journal of Psychosocial Rehabilitation, 2020)
This report presents the results of a study to determine the anti-inflammatory properties of the recommended Ortof-S tablets in comparison with its ingredients in separate dosage forms according to the Cotton pellet method. The preparation combines a non-steroidal anti-inflammatory drug with an antiulcer, an inhibitor of H +, K + -ATPase.